miR-132 overexpression is associated with modulation in miR-21 expression and glioblastoma cell behavior - Kimia Abdi; Hadi Bayat; Seyed Javad Mowla (PLoS ONE, 2026)
Glioblastoma multiforme (GBM) is the most aggressive and lethal primary tumor of the central nervous system. MicroRNAs (miRNAs) are key post transcriptional regulators of gene expression, and increasing evidence suggests that miRNA relationships may contribute to regulatory complexity in cancer biology. In this study, we combined in silico analyses of ten independent miRNA expression datasets (TCGA and GEO) with functional validation in GBM cell models to investigate the association between miR-132 and miR-21 in GBM. Differential expression analysis consistently demonstrated significant overexpression of miR-21-5p and downregulation of miR-132-3p in GBM tissues compared with normal brain. These findings were validated in U87 and C6 GBM cell lines using qRT-PCR, confirming consistent dysregulation of both miRNAs in vitro (p < 0.05). Functional experiments demonstrated that miR-132 overexpression is associated with reduced miR-21 expression and increased expression of established miR-21 target genes, including BMPR2 and BCL11B at both mRNA and protein levels. These molecular changes were accompanied by reduced metabolic activity, impaired wound closure, and increased apoptotic cell death in both U87 and C6 GBM models. Collectively, these findings support a strong functional association between miR-132 expression and miR-21 related regulatory networks and phenotypic changes in GBM. However, the present study does not provide evidence for a direct physical or fundamental interaction between miR-132 and miR-21. Further mechanistic studies, including rescue experiments and direct binding assays, are required to clarify the underlying regulatory mechanisms.